Validation of a Hybrid Exoskeleton for Upper Limb Rehabilitation. A Preliminary Study - Isabel-María Alguacil-Diego; Alicia Cuesta-Gómez; Aldo-Francisco Contreras-González; David Pont-Esteban; David Cantalejo-Escobar; Miguel Ángel Sánchez-Urán; Manuel Ferre (Sensors, 2021)
Recovery of therapeutic or functional ambulatory capacity in patients with rotator cuff injury is a primary goal of rehabilitation. Wearable powered exoskeletons allow patients to perform repetitive practice with large movements to maximize recovery, even immediately after the acute event. The aim of this paper is to describe the usability, acceptability and acceptance of a hybrid exoskeleton for upper-limb passive rehabilitation using the System Usability Scale (SUS) questionnaire. This equipment, called ExoFlex, is defined as a hybrid exoskeleton since it is made up of rigid and soft components. The exoskeleton mechanical description is presented along with its control system and the way motion is structured in rehabilitation sessions. Seven patients (six women and one man) have participated in the evaluation of this equipment, which are in the range of 50 to 79 years old. Preliminary evidence of the acceptance and usability by both patients and clinicians are very promising, obtaining an average score of 80.71 in the SUS test, as well as good results in a questionnaire that evaluates the clinicians’ perceived usability of ExoFlex.